Anatomical and Pathological Terms in Akkadian, Part IV - Adamson, P. В.
erimmatu, ZI.ḪA.ZA, ušultu (ÚŠ), mušarû, mašru (TEMEN.ŠÀ), išiltu, šapūlu, рēmu, umṣātu, terku, ḫalû/ḫālu, ṣiba/uru, uṭṭe/atu, še’u, kittab/pru, ṣētum (UD.DA), ummu.